The Influence of Service Quality on Patient Satisfaction in the JKN Era Using HCAHPS Indicators - Sumarni (Mulawarman International Conference on Tropical Public Health, 2025)
Background : The need for access to excellent healthcare services is a primary need for society. As the standard of living improves, so do the public's demands for higher health values. Therefore, hospitals are required to continuously improve the quality of their services to ensure consumer satisfaction. In order to provide fair and equitable healthcare services for all Indonesians, the government has implemented the National Health Insurance (JKN) program, administered by the Social Security Agency (BPJS). Objective : This study aims to determine the influence of service quality on patient satisfaction in the JKN Era at Inpatient Facilities in both Public and Private Hospitals. Research Methods/ Implementation Methods : This study is a quantitative research using an analytical observational study with a cross-sectional design. The sample consists of 131 respondents, with 78 respondents from public hospitals and 53 respondents from private hospitals. Results : The results of the study indicate that there is no significant difference in patient satisfaction levels using the HCAHPS method between private and public hospitals in Bantul Regency. This is evidenced by a significance value of 0.265, which is greater than 0.05. According to Table 4.5, there is also no significant difference across all HCAHPS components. These components include nurse communication, with a significance value of 0.403 (>0.05), doctor communication (0.789 > 0.05), hospital environment (0.896 > 0.05), pain management (0.129 > 0.05), communication about medications (0.179 > 0.05), discharge information (0.79 > 0.05), overall hospital rating (0.591 > 0.05), and willingness to recommend the hospital (0.622 > 0.05). All components of healthcare service delivery in both private and public hospitals fall into the "good" category. In terms of respondent satisfaction levels, 52.8% of respondents in private hospitals reported feeling very satisfied, while 47.2% felt satisfied. In public hospitals, 58.8% of respondents reported feeling very satisfied, and 41.2% felt satisfied. Conclusion/Lesson Learned : Based on the results of the study on the differences in patient satisfaction levels using the HCAHPS method in both private and public hospitals in Bantul Regency, it was found that patients were satisfied with the healthcare services provided by both types of hospitals. Furthermore, there was no significant difference in patient satisfaction levels between private and public hospitals in Bantul Regency. It is recommended that both private and public hospitals continue to improve and maintain healthcare services, particularly in doctor-patient communication, pain management provided to patients, and overall hospital management, to ensure greater patient satisfaction with the services provided.